2021
DOI: 10.3390/horticulturae7070192
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Effect on Growth-Related Parameters and Evaluation of Portulaca oleracea as a Phytoremediation Species in a Cr(VI)-Spiked Soil

Abstract: In a pot experiment, we assessed the potential of purslane (Portulaca oleracea) as a phytoremediation species in Cr(VI)-contaminated soils. We focused on the evaluation of phytotoxic Cr(VI) effects at concentrations reaching 150 mg Cr(VI) kg−1 and the possible stress amelioration effect of nitrogen on Cr(VI)-stressed plants. Treatments were T-0 (control), T-1 (25 mg Cr(VI) kg−1), T-2 = 50 mg kg−1, T-3 = 100 mg kg−1, and T-4 = 150 mg kg−1. We measured Cr(VI) concentration in aerial and root tissues, a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…One week prior to the harvest date, we measured plant height (cm), and photosynthetic rate (µmol CO 2 m −2 s −1 ) at a constant light intensity of 250 µmol cm −2 s −1 using the LI-Cor LI-6400XT Portable Photosynthesis System (LI-Cor, Lincoln, NE, USA)), whereas chlorophyll content (SPAD index) was measured using the OPTI-SCIENCES CCM-200 plus chlorophyll content meter (Opti-sciences, Hudson, NH, USA). Moreover, we measured the leaf area with the use of LI-3100C Area Meter (LI-COR Biosciences; Hellamco S.A., Athens, Greece) (all plant measurements are described in detail by [ 13 , 22 ]. At the end of the experiment, the aerial plant biomass was cut 2 cm above the soil surface and separated into leaves and stems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One week prior to the harvest date, we measured plant height (cm), and photosynthetic rate (µmol CO 2 m −2 s −1 ) at a constant light intensity of 250 µmol cm −2 s −1 using the LI-Cor LI-6400XT Portable Photosynthesis System (LI-Cor, Lincoln, NE, USA)), whereas chlorophyll content (SPAD index) was measured using the OPTI-SCIENCES CCM-200 plus chlorophyll content meter (Opti-sciences, Hudson, NH, USA). Moreover, we measured the leaf area with the use of LI-3100C Area Meter (LI-COR Biosciences; Hellamco S.A., Athens, Greece) (all plant measurements are described in detail by [ 13 , 22 ]. At the end of the experiment, the aerial plant biomass was cut 2 cm above the soil surface and separated into leaves and stems.…”
Section: Methodsmentioning
confidence: 99%
“…Purslane ( Portulaca oleraceae ) is a wild edible plant that can be commercially cultivated in pristine soils and traded as it can be used as a gourmet raw or cooked salad. It has recently been tested as a potential species for use in phytoremediation if introduced to Cr(VI)-contaminated soils [ 13 , 14 ]. Moreover, the phytoremediation potential of the species has been reported by Kale et al [ 15 ], who suggested that hydroponically grown purslane may tolerate a high accumulation of Cr through the accumulation of proline and enhanced capacity of scavenging radical oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in rice production, the highest dry weight yield was most impacted by sufficient N availability; further, lowest yields were observed with N deficiency [122]. A study by Thalassinos et al [126] revealed that the addition of N significantly increased the plant height of Portulaca oleracea during the phytoremediation of Cr(VI)-contaminated soils.…”
Section: Importance Of Macronutrients and Micronutrients For Plant Gr...mentioning
confidence: 99%
“…Thalassinos et al [7] analyzed the potential of purslane (Portulaca oleracea) as a phytoremediation species in Cr(VI)-contaminated soils. They concluded that purslane showed potential as a species to be successfully introduced to Cr(VI)-laden soils.…”
mentioning
confidence: 99%